2007
DOI: 10.1111/j.1600-0609.2007.00996.x
|View full text |Cite
|
Sign up to set email alerts
|

GEMOX‐R regimen is a highly effective salvage regimen in patients with refractory/relapsing diffuse large‐cell lymphoma: a phase II study

Abstract: GEMOX-R is a new salvage regimen for DLCL with high activity and relatively safe toxicity profile, which can be offered to elderly patients not candidates of ASCT consolidation. The high efficacy of the regimen in this unfavorable population and also in immunocompromised situations warrant further investigation of this regimen in all salvage situations of this type of lymphomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 28 publications
(31 reference statements)
3
71
0
1
Order By: Relevance
“…In some cases, dramatic responses have been observed; however, in general these agents have shown modest activity in relapsed and refractory DLBCL, with overall response rates ranging from 11 to 47%, CR rates from 1 to 16% and median durations of remission generally in the 2-6 months range (Table 1). [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] For many of these agents, studying specific subtypes of DLBCL (for example, the activated B cell subtype), or cases in which the target of the agent is known to be present, will likely prove to be more effective than simply enrolling all DLBCL cases. Therefore, some subtypes of DLBCL may ultimately prove to be amenable to maintenance therapy post transplant.…”
Section: Modification Of Salvage Therapymentioning
confidence: 99%
“…In some cases, dramatic responses have been observed; however, in general these agents have shown modest activity in relapsed and refractory DLBCL, with overall response rates ranging from 11 to 47%, CR rates from 1 to 16% and median durations of remission generally in the 2-6 months range (Table 1). [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] For many of these agents, studying specific subtypes of DLBCL (for example, the activated B cell subtype), or cases in which the target of the agent is known to be present, will likely prove to be more effective than simply enrolling all DLBCL cases. Therefore, some subtypes of DLBCL may ultimately prove to be amenable to maintenance therapy post transplant.…”
Section: Modification Of Salvage Therapymentioning
confidence: 99%
“…As shown by the studies reported in Table I (12,16,17,25,26,28,29,33,35,(37)(38)(39), the addition of rituximab to salvage chemotherapy improves the response rate, without decreasing the mobilization and collection of PbSC. Moreover, the original reports provide evidence of the lack of significant toxicity due to the addition of rituximab to salvage chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity of these regimes is mainly hematological and they generally allow for the adequate collection of PbSC in the majority of patients. The second group is formed by the gemcitabinecontaining regimens, frequently associated with vinorelbine and/or platinum compounds (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). These regimens produce complete remission rates ranging from 21 to 43%, and are generally less toxic to bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…While improvements in first-line therapy have resulted in 67% of patients with DLBCL being in a disease-free state 4 years following diagnosis, one-third of patients with DLBCL will have disease that is refractory to initial R-CHOP (<50% decrease in tumor burden) or have a recurrence of their cancer after achieving complete remission (3). Due to the substantial number of patients who have refractory DLBCL, numerous second-line chemotherapy regimens have been developed for the treatment of DLBCL; however, the complete response (CR) rate for these regimens is poor, ranging between 16 and 62% (Table I) (4)(5)(6)(7)(8). Additionally, a number of the second-line regimens for refractory DLBCL have significant side effect profiles (Table I); therefore, novel treatment approaches are required.…”
Section: Introductionmentioning
confidence: 99%